Ética profesional y percepción de la corrupción del contador público de la ciudad de Iquitos 2022 - Hauxwell Rodríguez, Carlos Santiago (2024)
The objective of the research presented was to determine the relationship between professional ethics and the perception of corruption of the public accountant of the city of Iquitos 2022. An applied study of a descriptive correlational level was used with a non-experimental design, working with a population of 1677 collegiate accountants from which a sample of 313 was extracted, they were used in a questionnaire for data collection. According to the results obtained, 23% of accountants have medium-level professional ethics, as there is evidence of a lack of consistency with ethical principles, a clear resistance to providing information honestly. For their part, 23% of chartered accountants perceive a very low level of corruption, since, although they recognize that corruption can affect the integrity of citizens, many of them fully agree with completing documentation using false data when this it is convenient for them. Finally, it was determined that there is a significant relationship between the variables, the same that was corroborated by a Spearman's Rho coefficient of 0.878, this being considerable positive.